Characterization of non-graphitized carbon blacks: a model with surface crevices. Issue 22 (26th May 2021) - Loi, Quang K.; Horikawa, Toshihide; Do, D. D.; Nicholson, D.
Abstract : Structure of adsorbate on a homogeneous surface and a creviced surface. Abstract : Experimental isotherms for argon and nitrogen adsorption on two non-graphitized carbon substrates, Carbopack B and Cabot BP280, do not obey Henry's Law in the range of pressures accessible to the most sensitive MKS pressure transducers. At high pressures, close to the bulk coexistence pressure ( P 0 ), the isotherms at temperatures below the bulk triple point temperature cross the P 0 axis at a finite loading, a behaviour which is interpreted as incomplete wetting. It was found that the adsorbed density at P 0 for Cabot BP280 is lower than that for Carbopack B which is, in turn, only slightly lower than that for the highly graphitized Carbopack F, suggesting that there is a long-range effect of the surface structure in non-graphitized carbon blacks, in the accumulation of higher layers, especially for Cabot BP280. We have carried out extensive Monte Carlo simulations to compare experimental observations with a molecular model for substrate surfaces decorated with crevices of molecular dimensions. From the analysis of the experimental data, it was found that the typical width of crevices is of the order of 0.65–0.9 nm. In the high pressure region, the crossing of the P 0 axis by isotherms at temperatures below the bulk triple point temperature can be explained by an adsorbate structure which is less dense and more disordered than the fcc structure of the bulk crystal, with a consequent raising of the coexistence pressure between the adsorbate and the gas phase above P 0 . Adsorbate loading at the point where the isotherm crosses the P 0 axis for Cabot BP280 is lower than for Carbopack B which can be attributed to a higher concentration of crevices leading to a lower adsorbate density and an irregular arrangement of atoms at the interface separating the adsorbed phase and the gas phase. This results in weaker gas-adsorbate interactions which supresses the build-up of higher layers. We suggest that the use of the adsorbed density at the bulk coexistence pressure, at temperatures below the bulk triple point temperature, can be a useful tool for assessing the presence and concentration of surface crevices on non-graphitized carbon black.